Responses of Bloom-Forming Heterosigma akashiwo to Allelochemical Linoleic Acid: Growth Inhibition, Oxidative Stress and Apoptosis - Wang, Renjun; Liu, Qian (Frontiers in Marine Science, 2022)
Algal blooms have been occurring in many regions worldwide, and allelochemicals are important algaecides used to control harmful algal blooms (HABs). The allelopathic effects of linoleic acid (LA) on the harmful raphidophyte Heterosigma akashiwo were studied, and the possible mechanisms were investigated through analyses of population growth dynamics, cellular ultrastructure and the physiological levels of H. akashiwo. The results showed that the inhibitory effect of LA on H. akashiwo cells increased with an increasing LA concentration. The levels of ROS and MDA were significantly elevated, indicating oxidative stress and lipid peroxidation due to LA exposure. At the same time, linoleic acid also induced the responses of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and POD, and nonenzymatic antioxidants such as reduced AsA and glutathione (GSH). Transmission electron microscopy revealed that the morphology of the algal cells was impaired in a LA-dependent manner. LA exposure decreased the cellular mitochondrial membrane potential, increased the release of cytochrome c, elevated the Bax to Bcl-2 ratio and activated caspase-3 and caspase-9, indicating that the expression of these regulators can trigger cell apoptosis. It was concluded that LA shows allelopathic effects on H. akashiwo, inducing physiological and morphological changes and finally triggering the apoptosis of H. akashiwo. All of these results showed that LA might have potential as an algaecide to control harmful algae.